Field reports, Pam and Reid Allen, August - November 1989 - Allen, Pamet al; Allen, Reid I.et al (1989)
Field reports contributed by Pam and Reid Allen with several other observers with additional notes about some sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1989. Epson - sheet feed